HUBUNGAN ANTARA PENGAWASAN, PROSEDUR KERJA DAN KONDISI FISIK DENGAN TERJADINYA KECELAKAAN KERJA PADA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT PERMATA BUNDA MEDAN TAHUN 2017 - Nur Azizah; Setiawan Setiawan; Gerry Silaban (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
A hospital is one of the work places which potentially causes danger to its employees. The cases which commonly occur are pricked by hypodermic needles, sprained, lumbago, and the other infections. A survey conducted a the beginning of 2017 revealed that there were some cases of occupational accident undergone by nurses at Permata Bunda Hospital such as HNP (Hernias Nukleus Pulposus), pricked by hypodermic needles, scratched by ampoule lids, and slipped. Methods: The objective of the research was to analyze the correlation of supervision, work procedure, and physical condition with the incidence of occupational accident in nurses in the inpatient wards of Permata Bunda Hospital, Medan. The data were analyzed by using chi square test. The samples were 96 nurse practitioners as the respondents, taken by using consecutive sampling technique. Results and Discussion: The result of the research showed that 17.7% of the respondents had undergone occupational accidents such as HNP (14.6%), pricked by hypodermic needles (15.6%), and slipped (10.4%). The result of chi square statistic test showed that the three variables: supervision (p=0.000), work procedure (p=0.005), and physical condition (p=0.000) had significant correlation with nurses' occupational accidents. Conclusion: It is recommended that the hospital management increase occupational safety and health for the nurses by providing training about the danger of occupational accident in nurses and about occupational safety and health.Keywords: Supervision, Work Procedure, Physical Condition, Occupational Accident